Adjuvant nivolumab plus ipilimumab or nivolumab alone versus placebo in patients with resected stage IV melanoma with no evidence of disease (IMMUNED): final results of a randomised, double-blind, phase 2 trial. Issue 10358 (1st October 2022) - Livingstone, Elisabeth; Zimmer, Lisa; Hassel, Jessica C; Fluck, Michael; Eigentler, Thomas K; Loquai, Carmen; Haferkamp, Sebastian; Gutzmer, Ralf; Meier, Friedegund; Mohr, Peter; Hauschild, Axel; Schilling, Bastian; et al.
Summary: Background: The IMMUNED trial previously showed significant improvements in recurrence-free survival for adjuvant nivolumab plus ipilimumab as well as for adjuvant nivolumab alone in patients with stage IV melanoma with no evidence of disease after resection or radiotherapy. Here, we report the final analysis, including overall survival data. Methods: IMMUNED was an investigator-sponsored, double-blind, placebo-controlled, three-arm, phase 2 trial conducted in 20 academic medical centres in Germany. Eligible patients were aged 18–80 years with stage IV melanoma with no evidence of disease after surgery or radiotherapy. Patients were randomly assigned (1:1:1) to either nivolumab plus ipilimumab (nivolumab 1 mg/kg plus ipilimumab 3 mg/kg every 3 weeks for four doses followed by nivolumab 3 mg/kg every 2 weeks), nivolumab monotherapy (nivolumab 3 mg/kg every 2 weeks), or matching placebo, for up to 1 year. The primary endpoint was recurrence-free survival in the intention-to-treat population. Secondary endpoints were time-to-recurrence, overall survival, progression-free survival or recurrence-free survival 2 (in patients in the placebo group who crossed over to nivolumab monotherapy after experiencing disease recurrence), and safety endpoints. This trial is registered on ClinicalTrials.gov (NCT02523313 ), and is complete. Findings: Between Sept 2, 2015, and Nov 20, 2018, 175 patients were enrolled in the study, and 167 were randomly assigned to receive either nivolumab plus ipilimumab (n=56), nivolumab plus ipilimumab-matching placebo (n=59), or double placebo control (n=52). At a median follow-up of 49·2 months (IQR 34·9–58·1), 4-year recurrence-free survival was 64·2% (95% CI 49·2–75·9) in the nivolumab plus ipilimumab group, 31·4% (19·7–43·8) in the nivolumab alone group, and 15·0% (6·7–26·6) in the placebo group. The hazard ratio (HR) for recurrence for the nivolumab plus ipilimumab group versus placebo was 0·25 (97·5% CI 0·13–0·48; p<0·0001), and for the nivolumab group versus placebo was 0·60 (0·36–1·00; p=0·024). Median overall survival was not reached in any treatment group. The HR for overall survival was significantly in favour of the nivolumab plus ipilimumab group versus placebo (HR 0·41; 95% CI 0·17–0·99; p=0·040), but not for the nivolumab group versus placebo (HR 0·75; 0·36–1·56; p=0·44). 4-year overall survival was 83·8% (95% CI 68·8–91·9) in the nivolumab plus ipilimumab group, 72·6% (57·4–83·2) in the nivolumab alone group, and 63·1% (46·9–75·6) in the placebo group. The median progression-free survival or recurrence-free survival 2 of patients in the placebo group who crossed over to nivolumab monotherapy after experiencing disease recurrence was not reached (95% CI 21·2 months to not reached). Rates of grade 3–4 treatment-related adverse events remained largely unchanged compared with our previous report, occurring in 71% (95% CI 57–82) of the nivolumab plus ipilimumab group, and 29% (95% CI 17–42) of patients receiving nivolumab alone. There were no treatment-related deaths. Interpretation: Both active regimens continued to show significantly improved recurrence-free survival compared with placebo in patients with stage IV melanoma with no evidence of disease who were at high risk of recurrence. Overall survival was significantly improved for patients receiving nivolumab plus ipilimumab compared with placebo. Use of subsequent anti-PD-1-based therapy was high in patients in the placebo group after recurrence and most likely impacted the overall survival comparison of nivolumab alone versus placebo. The recurrence-free and overall survival benefit of nivolumab plus ipilimumab over placebo reinforces the change of practice already initiated for the treatment of patients with stage IV melanoma with no evidence of disease. Funding: Bristol-Myers Squibb.